O Formułowaniu się i Propagacji Płaskiej Fali Uderzeniowej w Biliniowym Ośrodku Sprężysto-Plastycznym - Włodarczyk, E. (Engineering Transactions, 1972)
In the paper is derived a closed form solution of the problem of formation and propagation of a stress shock wave in a bilinear elastic-plastic medium. Closed form formulae are given describing the form of the shock wave front. It is shown that the fields of stresses and displacement velocities substantially depend upon the manner in which the external load increases.